CHARACTERISTICS OF PROFESSIONAL-PEDAGOGICAL ACTIVITY DEVELOPMENT IN THE CONDITIONS OF INCLUSIVE EDUCATION (Conference Zone, 2022)
In this article, the characteristics of professional-pedagogical activities in the conditions of educational inclusion are studied from the pedagogical-psychological point of view. Together with this, the space of inclusive education, the conditions of inclusive education are described, and the components of structural and functional analysis of pedagogical activity are analyzed.